Memoirs of the Museum of Victoria. - Museum of Victoria (Melbourne : Museum of Victoria, 1984)
Publishes papers on original research in the natural sciences pertinent to Victoria and/or the Museum's collections; papers in Australian Indigenous collections have main focus on Southern, Central and Northern Australia.
ISSN registration
Keywords: Natural history -- Australia -- Periodicals; Sites; Material culture; Research - Collections; Animals; Technology; Anthropology; Cultural heritage - Protection - Museums and keeping places - Collections and acquisitions; Australian seas; Victoria (Vic)